First-principles thermodynamic modeling for the Al-Nb-Ni ternary system - Arkapol Saengdeejing; Ryoji Sahara; Yoshiaki Toda (Science and Technology of Advanced Materials: Methods)
In CALPHAD methodology, used for thermodynamic database construction, the first-principles calculations based on the density functional theory have increasingly become important tool to provide an input data for assessing the thermodynamic database. As the advancement in computational power, it is evident that the first-principles calculations has become integral part for determining the thermodynamic properties of the phases within the multi-component system than the time consuming and costly experimental procedures. The alloys development process can be significantly accelerated, especially in the complex multi-component systems. With first-principles data for both end-members thermodynamic descriptions and interaction parameters, the Al-Nb-Ni ternary thermodynamic database construction can be rapidly established. Without relying on any experimental data for solid-state phases, the first-principles Al-Nb-Ni thermodynamic database can exhibits most of the features comparing with the experimental phase diagram.